Assistive technologies that support social interaction in long-term care homes: a scoping review protocol. Issue 3 (March 2020) - Macdonald, Marilyn; Martin-Misener, Ruth; Weeks, Lori; Moody, Elaine; McKibbon, Shelley; Wilson, Beth; Almukhaini, Salma; Stratton, Lillian
ABSTRACT: Objective: The objective of this scoping review is to chart the literature on assistive technologies that support social interaction (excluding robots) used with older adults in long-term care (LTC). Introduction: The need for LTC in institutional settings is in high demand. Loneliness and social isolation are common in these settings. Technology holds potential to contribute to mitigation of loneliness. As there are no systematic reviews examining forms of assistive technologies to support social interaction other than robots, used within LTC settings, there is a need to categorize the current research regarding such technologies to inform practice, policy and any need for further research. Inclusion criteria: The review will consider studies based in LTC institutional settings with participants (≥65 years), institutional staff and visiting family members Methods: The JBI methodology for scoping reviews will be employed. This includes a three-step search strategy: i) identify keywords from CINAHL and PsycINFO, ii) conduct a second search using all identified keywords across select databases, and iii) screen the reference lists of all included articles and reports for additional studies. Titles and abstracts will be screened by two independent reviewers. Full text of selected citations will be assessed against inclusion criteria by two independent reviewers. A data extraction tool will be used, and extracted data will be presented in a narrative accompanied by diagrams or tables that reflect the objective of the review.